Utilization of open space – tale of two cities - Wahid, Julaihi (2008)
People’s experience is a significant factor in the development of urban activities in the city. The provisions of open space are considered as a “lung” of the city whilst the urban structure as the nerve. The integration of these two factors can give “life” to the city. The city council maintained the idea of extending the open spaces by implementing designing principles in the new development. However, do the location and the provisions of the urban street furniture really fit the need of the urbanites? By taking examples from two cities i.e. Medan, Indonesia and Georgetown, Penang, this paper emphasize on the aspects of space utilization and analyzed the passive or active activities taken place here. The city of Medan was the product of the Dutch whilst Georgetown was the remnants of the British. The urban design of the cities resembles that of the Western principles. The size and location of these open spaces were suitable to the past requirements during the early period. The paper also delineates the potentials and problems of the linkage in the city. It is believed that the success and failure of the open space in the city is very much related to the primary and secondary intertwine of usage in the city.